A Study on Isolation of Group A Beta Hemolytic Streptococci and its Sensitivity to Co-Amoxiclav in Acute Tonsillitis - Ghimire , Bibek; Chandra Rijal, Krishna; Prasad Koirala, Krishna; Raj Kafle, Binaya; Gautam , Shreya; Shrestha , Rajani; Shrestha , Nischal; Dhungana , Aakrti (Nepal Journal of Medical Sciences, 2025)
Introduction: Acute tonsillitis, often caused by Group A Beta-Hemolytic Streptococci (GABHS), is a significant global health concern. Co-Amoxiclav is widely used for treatment, but rising antibiotic resistance necessitates evaluation of its efficacy. This study aimed to isolate GABHS and assess its sensitivity to Co-Amoxiclav in patients with acute tonsillitis. Methods: A hospital-based cross-sectional study was conducted at Manipal Teaching Hospital, Nepal, from November 2023 to January 2025 after obtaining ethical clearance (MCOMS/IRC/574/GA). Throat swabs from 280 clinically diagnosed patients with acute tonsillitis were collected and analyzed for bacterial pathogens. Antimicrobial susceptibility testing was performed, and data were analyzed using SPSS. Results: Out of 280 clinically diagnosed patients with acute tonsillitis, GABHS was isolated in 12.85% of cases, with 77.77% sensitivity to Co-Amoxiclav. The chi-square test (p-value = 0.80) indicated no significant difference, suggesting Co-Amoxiclav's effectiveness regardless of GABHS presence in bacterial tonsillitis. Azithromycin showed the highest resistance, while vancomycin was the most effective. Conclusions: GABHS remains a key pathogen in acute tonsillitis, and Co-Amoxiclav is still effective for treatment. However, declining sensitivity underscores the need for judicious antibiotic use and exploration of alternative treatments.